Harmonizing Baduy Customary Law with Human Rights and Religious Freedom - Zaenudin, Zaenudin; Saepudin, Eli Apud (SASI, 2026)
Introduction: Baduy customary law is a system of norms that governs the social, spiritual, and ecological life of the Baduy people in Banten. The uniqueness of this customary law lies in its adherence to the principle of pikukuh karuhun (ancestral rules), which rejects modernization and maintains the sanctity of tradition. However, in the context of a modern state that upholds human rights and religious freedom, questions arise as to the extent to which Baduy customary law can coexist with universal human rights principles, particularly the rights to freedom of religion and expression. Purposes of the Research: This study aims to analyze the compatibility between Baduy customary law and human rights principles, as well as to examine the dynamics of the relationship between indigenous communities and the state in maintaining a balance between collective and individual rights. The research method used is a juridical-sociological approach with data collection techniques through literature studies, interviews, and field observations in the Inner Baduy and Outer Baduy regions. Methods of the Research: Using a juridical-sociological approach, with data collection techniques through literature studies, in-depth interviews, and field observations in the Inner Baduy and Outer Baduy regions, in order to understand the relationship between customary law, human rights, and religious freedom contextually. Results of the Research: This research reveals that Baduy customary law, while seemingly restrictive, is fundamentally oriented toward spiritual values. The state needs to adopt a multicultural and recognition-based approach to protect the rights of indigenous peoples without negating human rights principles. Integrating customary law into the national legal framework is key to achieving contextual and inclusive justice.